Evaluasi Kerasionalan Penggunaan Obat Antihipertensi Pada Pasien Hipertensi Rawat Inap RSUD H. Hanafie Muara Bungo - Tri Wasilah; Rasmala Dewi; Deny Sutrisno (Indonesian Journal of Pharmaceutical Education, 2022)
According to the World Health Organization (WHO), hypertension affects 22% of the world's population. Hypertension is also the cause of death with 23.7% of the total 1.7 million deaths in Indonesia in 2016. Based on the medical record sheet at H. Hanafie Muara Bungo Hospital there are 313 people with hypertension and 78 are included in the inclusion criteria. The aim is to find out the rationale for using antihypertensive drugs at the H. Hanafie Muara Bungo Hospital for the 2019 period in the form of choosing the right drug, right drug indication, right dose and right frequency of administration. The aim is to find out the rationale for using antihypertensive drugs at the H. Hanafie Muara Bungo Hospital for the 2019 period in the form of choosing the right drug, right drug indication, right dose and right frequency of administration. The research method is descriptive observational with data collection using purposive sampling technique. The results on the use of antihypertensive drugs that are most often used are amlodipine CCB (Calcium Channel Blockers) class. Characteristics such as gender have the same percentage, namely 39 patients (50%), hypertension occurs mostly in the age range 56-65 years, and the most diagnosis is stage 2 hypertension (37.2%). Percentage of rational use of antihypertensive drugs from right drug selection 78 patients (85.9%), right drug indication as many as 78 patients (100%) right, right dose 78 patients (100%) right, and the right frequency of drug administration 78 patients (100%) right. The conclusion of this study is the rationale for the use of the most widely used antihypertensive drug is amlodipine, the right choice of drug is 100%, the right drug indication is 100%, the dose is 100% right, and the frequency is 100%.